Keragaman Cendawan Rizosfer dan Potensinya sebagai Agens Antagonis Fusarium oxysporum Penyebab Penyakit Layu Tanaman Krisan - Engla Yona Liza; Adrinal Adrinal; Jumsu Trisno (Jurnal Fitopatologi Indonesia, 2015)
Plant rhizosphere is rich of microbes, one of these is a group of fungi. This research aimed to obtain fungi isolates from rhizosphere of healthy Chrysanthemum, followed by evaluation of their potential as biocontrol agents of Fusarium oxysporum. Isolation of fungi rhizosphere was based-on serial dilution method. As many as 6 isolates of rhizosphere fungi was succesfully isolated with diverse characters. Pathogenicity test showed that 6 isolates were not pathogenic because it did not cause wilt symptoms on Chrysanthemum. The selected isolates were subjected to in vitro assay for their potential as biocontrol agents, 4 isolates had antagonist ability (46.42–51.61%) and antibiosis activity against F. oxysporum. Fungi isolates having the potential as biocontrol agents was identified as Trichoderma sp. (2 isolates), Penicillium sp., and Paecillomyces sp.